Linking corporate social responsibility, brand activism, and corporate reputation: The Portuguese case - Miranda, S.; Miguel, A. (Cases on developing effective research plans for communications and information science, 2022)
Corporate Social Responsibility (CSR) and, more recently, brand activism has become an important topic in business strategies, with companies playing an increasingly prominent role in socio-political life and addressing a wide range of social issues. However, the legitimacy of spending capital for investments in CSR and activism actions is not yet fully accepted by the business and academic world, with several companies and authors considering these expenses as unnecessary. As such, this chapter aims to highlight Portuguese empirical research that demonstrates how companies' social and environmental responsibility actions can impact their corporate reputation, based on a quantitative investigation carried out to 613 consumers of a company in the Portuguese energy sector. The results showed that CSR is one of the factors that has the greatest positive impact on corporate reputation, thus contributing to a better understanding of how companies' social investments can be a source of competitive advantage and benefit corporate performance. This chapter also helps to encourage other authors to study a recent line of research in the field of marketing – brand activism – which is still under development and, therefore, has a great potential to be explored.